Effect of filler loading and chemical modifications on properties of Chitosan/Polypropylene composites - Faisal Amri Tanjung (School of Materials Engineering, Universiti Malaysia Perlis, 2012)
The study was aimed to prepare chitosan filled polypropylene (PP) composites.